THE EXISTENCING OF A FEMALE WORKERS IN THE WORKSPLACE: IS THERE AN IMPROVING IN THE PERFORMANCE OF THE COMPANY - Meiliyah Ariani; Zulhawati; Hermiyetti; Andriansyah (Universitas prof. Dr. Moestopo (Beragama), 2022)
This study aims to obtain empirical evidence regarding the effect of the number of female workers in the workplace as measured by the number of gender, stress, emotion, patient, skill, and leadership on the success of the company as measured by profitability and productivity.nThe research method used is a descriptive qualitative approach. The data collection technique in the study was carried out based on theoretical studies from the search for research journals, books and papers. descriptive qualitative approach to describe how much influence the number of female workers in the workplace as measured by the number of gender, stress, emotion, patient, skill, and leadership has on the success of the company as measured by profitability and productivity The search results from several studies show that the number of female workers in the workplace has a significant effect on the profitability and productivity of the company, although the variable number of female workers in the workplace as measured by stress and emotion does not have a major influence on profitability and productivity.